WORKPLACE BULLYING EXPERIENCE AND TURNOVER INTENTIONS AMONG NURSES IN HOSPITALS IN SOUTH- WEST NIGERIA - Bolanle Lasisi, Kadijat; Olufunminiyi Olonade, Zaccheaus; Samson Odebode, Adebayo; Ojo, Solomon; Celinah Timi-Eweje, Aanu; Oyewale Shittu, Lateef (African Journal of Social and Behavioural Sciences, 2026)
Bullying is a major issue affecting service delivery and the effectiveness of nurses in Nigeria. However, the study examined workplace bullying experiences and turnover intentions among nurses in hospitals in South-western Nigeria. The study data were collected using a structured questionnaire. Purposive sampling technique was used to select hospitals in the South- west region of Nigeria, in which a total of six hundred and twenty-two (622) nurses were randomly selected for the study. Descriptive and inferential statistics were used to analyse the data collected. The collected data were analysed at 0.05 alpha level. The results of the study showed that bullying significantly influenced turnover intentions among nurses in hospitals in South-western Nigeria (F(1, 418) = 5.708, p < .005). It was concluded that workplace bullying experience was a predictor of turnover intentions, and that selected hospitals should formulate and implement a comprehensive workplace anti-bullying policy that clearly defines bullying behaviours and outlines its consequences for perpetrators.